Parental psychiatric disorders and age-specific risk for offspring major depression: Finnish nationwide register-based study - Upadhyaya, Subina; Sucksdorff, Dan; Koskela, Miina; Cheslack-Postava, Keely; Brown, Alan S.; Sourander, Andre (Cambridge University Press (CUP), 2025)
Background: Limited studies have examined the association between the whole range of parental psychopathology and offspring major depression (MD). No previous study has examined this association by age of onset of offspring MD, or restricting to parental psychiatric diagnoses before offspring birth.
Methods: This nested case-control study included 37,677 cases of MD and 145,068 controls, identified from Finnish national registers. Conditional logistic regression models examined the association between parental psychopathology and MD, adjusting for potential confounders.
Results: Increased risk of MD, expressed as adjusted odds ratio and 95% confidence interval (aOR [95% CI]) were most strongly observed for maternal diagnoses of schizophrenia and schizoaffective disorders (2.51 [2.24-2.82]) and depression (2.19 [2.11-2.28]), and paternal diagnoses of schizophrenia and schizoaffective disorders (2.0 [1.75-2.29]) and conduct disorders (1.90 [1.40-2.59]). The aORs for any psychiatric diagnosis were (2.66 [2.54-2.78]) for mothers, (1.95 [1.86-2.04]) for fathers, and (4.50 [4.24-4.79]) for both parents. When both parents had any psychiatric diagnosis, the highest risk was for MD diagnosed at the age of 5-12 years (7.66 [6.60-8.89]); versus at 13-18 years (4.13 [3.85-4.44]) or 19-25 years (3.37 [2.78-4.07]). A stronger association with parental psychopathology and offspring MD was seen among boys than girls, especially among 13-19 years and 19-25 years.
Conclusions: Parental psychiatric disorders, including those diagnosed before offspring birth, were associated with offspring MD, indicating potential genetic and environmental factors in the development of the disorder.